KARAKTERISTIK PENGERINGAN DAGING BUAH PALA (Myristica fragrans houtt) MENGGUNAKAN ALAT PENGERING TENAGA SURYA TIPE TENDA - Muara Dewa Taarae; Frans Wenur; Ireine A. Longdong (COCOS, 2019)
ABSTRACT The drying of the nutmeg using a tent-type solar dryer has been carried out in order to determine the drying characteristics of the nutmeg flesh and to determine the drying efficiency. The results showed that the drying process of the material to reach a moisture content of 12-14% took 19 hours with the average solar radiation intensity on days 1, 2, and 3 being 429.06 W/m2, 446.16 W/m2, and 560.13 W/m2. This intensity resulted in temperature changes for the material temperature and room temperature of the dryer on days 1, 2 and 3 which ranged from respectively (38.5 oC and 32.88 oC), (41.5 oC and 32.88 oC), and (43.5 oC and 32.46 oC). The average humidity of the air inside and outside the dryer on days 1, 2, and 3 are (80.62% and 83.19%), (76.34% and 79.50%), and (81.19% and 81.41%). The drying rate of the nutmeg flesh for days 1, 2, and 3 varied with an initial moisture content of 85.26% (bb). The results of the calculation of drying efficiency on day 1, 2, and 3 were 28.09%, 9.03% and 2.33%, respectively. Key words: Drying characteristics, radiation intensity, drying efficiency.